The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2147/ijgm.s325365
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Risk Factors for Delirium in Elderly Patients in the Emergency Rooms and Intensive Care Unit of the National Geriatric Hospital Emergency Department: A Cross-Sectional Observational Study

Abstract: Purpose: To diagnose delirium and identify risk factors for its development in elderly patients in the emergency department (ED) and intensive care units (ICU) at the National Geriatric Hospital (Vietnam). Patients and Methods: A cross-sectional observational study was conducted with a convenience sample of non-surgical patients admitted to ED and ICU at Hanoi National Geriatric Hospital in Vietnam. In total, 163 patients met the selection criteria and were included in the study. Screening involved using the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…It has been found that hearing impairment has an effect on the development of delirium. There are studies reporting that hearing impairment is an important risk factor for delirium 40,41 . It was found that, among all ICUs, being hospitalized in the internal ICU had an 11.84 times greater effect on the development of delirium than being treated in the coronary ICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that hearing impairment has an effect on the development of delirium. There are studies reporting that hearing impairment is an important risk factor for delirium 40,41 . It was found that, among all ICUs, being hospitalized in the internal ICU had an 11.84 times greater effect on the development of delirium than being treated in the coronary ICU.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies reporting that hearing impairment is an important risk factor for delirium. 40,41 It was found that, among all ICUs, being hospitalized in the internal ICU had an 11.84 times greater effect on the development of delirium than being treated in the coronary ICU. This may be because of the structure of the coronary ICU in the institution where the study was conducted.…”
Section: B Level Of Sedation and Level Of Consciousnessmentioning
confidence: 99%
“…2 Its consequences are highly deleterious in patients since it causes more days of mechanical ventilation, longer stay in Intensive Care Units (ICU), higher risk of infections and even higher mortality. 3 , 4 Thus, it is important to prevent delirium, starting with its timely detection, 5 since this is one of the main measures for its prevention and treatment. 6 , 7 The Pain, Agitation and Delirium (PAD) guidelines, 8 the ABCDEF bundle 9 and the Humanizing Intensive Care Units (HU-CI) project 10 confirm that the assessment of delirium using validated scales should be performed frequently so that timely preventive measures can be developed, even from the suspicion or probability of its presence.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major determinants of delirium is old age [ 7 ]. In addition, risk factors include severity of illness, previous dementia, malnutrition, emergency surgery or trauma prior to ICU admission, mechanical ventilation, and anxiety [ 8 , 9 , 10 ]. There are also risk factors that are modifiable.…”
Section: Introductionmentioning
confidence: 99%